Effect of Particle Size and Shape on Wall Slip of Highly Filled Powder Feedstocks for Material Extrusion and Powder Injection Molding - Sanetrnik, Daniel; Hausnerova, Berenika; Novak, Martin; Mukund, Bhimasena Nagaraj (3D printing and additive manufacturing, 2023)
A necessity to distinguish between the influence of powder shape and size (particle size distribution) is especially demanding for highly filled metal powder feedstocks employed in additive manufacturing and powder injection molding. As their processability is evaluated through rheological behavior, the study focuses on the effect of powder size/shape on a wall slip, which is a typical phenomenon determining flow performance of these materials. Water and gas atomized 17-4PH stainless steel powders with D 50 of about 3 and 20 μm are admixed into a binder containing low-density polyethylene, ethylene vinyl acetate, and paraffin wax. Mooney analysis to intercept the slip velocity of 55 vol. % filled compounds reveals that wall slip effect appears to vary significantly with size and shape of metal powders-round shaped and large particles are the most prone to the wall slip. However, the evaluation is affected by the type of the flow streams resulting from the geometry of the dies-conical dies reduce the slip up to 60% in case of fine and round particles.
Keywords: wall slip; powder shape; material extrusion; powder injection molding; highly filled feedstock; die geometry; particle size